2005
DOI: 10.1099/vir.0.81230-0
|View full text |Cite
|
Sign up to set email alerts
|

Open reading frame 73 is required for herpesvirus saimiri A11-S4 episomal persistence

Abstract: Herpesvirus saimiri (HVS) establishes a latent infection in which the viral genome persists as a non-integrated episome. Analysis has shown that only open reading frames (ORFs) 71-73 are transcribed in an in vitro model of HVS latency. ORF73 also colocalizes with HVS genomic DNA on host mitotic chromosomes and maintains the stability of HVS terminal-repeat-containing plasmids. However, it is not known whether ORF73 is the only HVS-encoded protein required for episomal maintenance. In this study, the elements r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Functional analysis of HVS episomal persistence using mutants lacking all latency-associated genes (i.e., ORF71, -72, and -73) demonstrated that these genes are required for the ability of HVS to sustain episomal maintenance (8). Moreover, replacement of ORF73 alone rescued HVS episomal persistence to wild-type levels (8).…”
mentioning
confidence: 99%
“…Functional analysis of HVS episomal persistence using mutants lacking all latency-associated genes (i.e., ORF71, -72, and -73) demonstrated that these genes are required for the ability of HVS to sustain episomal maintenance (8). Moreover, replacement of ORF73 alone rescued HVS episomal persistence to wild-type levels (8).…”
mentioning
confidence: 99%
“…This association is mediated by ORF73, a LANA homologue, which binds to the HVS terminal repeats and interacts with mitotic chromosomes through its C terminus (10,11,52). The similarities between LANA and ORF73 prompted Griffiths and Whitehouse to investigate the ability of MeCP2 and DEK to mediate HVS episome maintenance.…”
mentioning
confidence: 99%
“…Moreover, upon infection, the viral genome persists as high-copy-number, circular, nonintegrated episomes that segregate to progeny cells upon division, a process that is mediated by the ORF73 episomal maintenance protein (22)(23)(24)(25). This not only reduces the risk of insertional mutagenesis and gene silencing by epigenetic mechanisms but also allows the HVS-based vector to stably transduce nondividing and dividing cell populations and provide sustained heterologous gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The viral genome exists as a stable circular episome separate from host DNA, thereby reducing the risk of insertional mutagenesis and gene silencing by epigenetic mechanisms. HVS can also persist in dividing cells, as the episomal DNA is able to replicate during latency and is transferred to daughter cells upon cell division via the open reading frame 73 (ORF73) episomal maintenance protein (22)(23)(24)(25). The virus has also been shown to efficiently infect and persist in three-dimensional multicellular spheroid cultures, a three-dimensional cell culture system that closely resembles a tumor, in addition to tumor xenografts in vivo (26)(27)(28).…”
mentioning
confidence: 99%
See 1 more Smart Citation